(untitled) (Research, Society and Development, 2020)
For the geotechnical design of building foundations, it is necessary to have knowledge about the structural elements and the characteristics of the supporting terrain. The allowable bearing soil capacity can be defined from a global safety factor linked to the bearing capacity of the soil. This article has the objective of presents a set of electronic spreadsheets developed using the VBA tool (Visual Basic for Applications), for calculating the bearing capacity and allowable bearing capacity of the soil through theoretical and semi-empirical methods and optimization of the geotechnical dimensioning of shallow foundations with square section. In order to verify the applicability of the developed program, it were considered hypotheses of variation of the settlement quota and the water level. The results achieved for the theoretical methods increase in the allowable stress value, as the level of support approaches the impermeable layer, however, for semi-empirical methods, the values remained the same, regardless of the depth change. The variation in the water level reduced considerable the allowable tension value, which can cause damage to the dimensioned foundation under this circumstance. The program proved to be intuitive and practical for academic and professional purposes, providing reduction in the calculation errors, since it optimizes the results and allows making safe and economical decision.